LincRNA‐p21 inhibits hepatic stellate cell activation and liver fibrogenesis via p21. (26th October 2015) - Zheng, Jianjian; Dong, Peihong; Mao, Yuqing; Chen, Shaolong; Wu, Xiaoli; Li, Guojun; Lu, Zhongqiu; Yu, Fujun
Abstract : Long non‐coding RNAs are involved in various biological processes and diseases. The biological role of long intergenic non‐coding RNA‐p21 (lincRNA‐p21) in liver fibrosis remains unknown before this study. In this study, we observed marked reduction of lincRNA‐p21 expression in mice liver fibrosis models and human cirrhotic liver. Over‐expression of lincRNA‐p21 suppressed activation of hepatic stellate cells (HSCs) in vitro . Lentivirus‐mediated lincRNA‐p21 transfer into mice decreased the severity of liver fibrosis in vivo . Additionally, lincRNA‐p21 reversed the activation of HSCs to their quiescent phenotype. The mRNA levels of lincRNA‐p21 and p21 were positively correlated. Our results show that over‐expression of lincRNA‐p21 promotes up‐regulation of p21 at both the mRNA and protein levels. Furthermore, lincRNA‐p21 inhibited cell‐cycle progression and proliferation of primary HSCs through enhancement of p21 expression. Compared with healthy subjects, serum lincRNA‐p21 levels were significantly lower in patients with liver cirrhosis, especially those with decompensation. These findings collectively indicate that lincRNA‐p21 is a mediator of HSC activation, supporting its utility as a novel therapeutic target for liver fibrosis. Abstract : LincRNA‐p21 expression was decreased in fibrotic liver tissues and in activated HSCs. Overexpression of lincRNA‐p21 inhibited activation of hepatic stellate cells (HSCs) in vitro . We further indicated that lincRNA‐p21 suppressed the cell cycle and proliferation of primary HSCs through enhancement of p21. Our findings propose a novel therapeutic target for liver fibrosis.